2014
DOI: 10.1021/bi401619q
|View full text |Cite
|
Sign up to set email alerts
|

Curvature Enhances Binding and Aggregation of Huntingtin at Lipid Membranes

Abstract: Huntington disease (HD) is a genetic neurodegenerative disease caused by an expanded polyglutamine (polyQ) domain in the first exon of the huntingtin (Htt) protein, facilitating its aggregation. Htt interacts with a variety of membraneous structures within the cell, and the first 17 amino acids (Nt17) of Htt directly flanking the polyQ domain comprise an amphiphathic α-helix (AH) lipid-binding domain. AHs are also known to detect membrane curvature. To determine if Htt exon 1 preferentially binds curved membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 78 publications
1
54
0
Order By: Relevance
“…The observed decreases in the magnitude of F min associated with disrupted regions of the bilayer are primarily due to a weakened adhesive interaction between the disrupted bilayer and the AFM tip. 28,47,48 The observed decrease in the magnitude of F max associated with disrupted regions of the bilayer indicates a decreased membrane rigidity or compression modulus. 28,47,48 Collectively, these results indicate that interaction between lipid bilayers and Aβ(1−40), independent of the preparatory history, results in regions of altered membrane morphology (increased roughness) and mechanical properties (decreased compression modulus of the bilayer and a weakened adhesive interaction between the tip and surface).…”
Section: Different Aβ(1−40) Preparation Protocols Alter Aggregation Kmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed decreases in the magnitude of F min associated with disrupted regions of the bilayer are primarily due to a weakened adhesive interaction between the disrupted bilayer and the AFM tip. 28,47,48 The observed decrease in the magnitude of F max associated with disrupted regions of the bilayer indicates a decreased membrane rigidity or compression modulus. 28,47,48 Collectively, these results indicate that interaction between lipid bilayers and Aβ(1−40), independent of the preparatory history, results in regions of altered membrane morphology (increased roughness) and mechanical properties (decreased compression modulus of the bilayer and a weakened adhesive interaction between the tip and surface).…”
Section: Different Aβ(1−40) Preparation Protocols Alter Aggregation Kmentioning
confidence: 99%
“…37 Specific features of these time-resolved tip/sample forces, the maximal tapping force (F max ) and minimal tapping force (F min ) per oscillation cycle, are sensitive to the mechanical properties of the surface and can be used to map relative changes in such properties along a surface with a high spatial resolution. 28,47,48 F max refers to the peak or largest repulsive (positive) force between the tip and surface associated with an individual tapping event, and F min is the largest magnitude attractive (negative) force experienced during a tapping event. Several numerical simulations and experimental studies have demonstrated that F max can be directly related to the compression modulus of the surface and that F min is sensitive to the adhesive interaction between the tip and surface.…”
Section: Different Aβ(1−40) Preparation Protocols Alter Aggregation Kmentioning
confidence: 99%
“…Due to their ability to weakly bind membranes, their interaction with membranes is easily regulated. Nt17 has been shown to sequester truncated htt exon 1 peptides to regions of curvature on supported lipid bilayers (81). The structure of an AH is compatible with the formation of a variety of helix bundles in aqueous environment that is driven by maximizing the interaction of the hydrophobic faces of adjacent helices (82, 83).…”
Section: Nt17 Structure In Monomeric and Aggregated Httmentioning
confidence: 99%
“…Nt17 facilitates the trafficking of htt exon 1 to membranes associated with the ER, autophagic vacuoles, mitochondria, and Golgi (14, 142). Membrane curvature sensing, facilitated by AH structural characteristics of Nt17, may play a mechanistic role in these functions (81). Additional evidence that Nt17 directly interacts with lipid membranes was provided by the observation that the binding of htt exon 1 to large unilamellar vesicles composed of phosphatidylcholines (PC) or a mixture of PC and phosphatidylserines (PS) enhanced the helical content of Nt17 (14).…”
Section: Nt17 Mediates Htt/lipid Interactions With Potential Implicatmentioning
confidence: 99%
“…The novel observation of slow-migrating AR species may reflect intrinsic features of specific AR functional domains. It may be that slow-migrating species have lipophilic properties, resulting from the presence of lipophilic hormone in the ligand-binding pocket, or from interactions with lipid membranes, as has been shown with other polyglutamine-expanded peptides (Burke et al, 2013b; Chaibva et al, 2014). Alternatively, the low density of slow-migrating species might arise from aberrant conformation of AR structural domains.…”
Section: Discussionmentioning
confidence: 99%